2024
DOI: 10.1111/add.16514
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and alcohol use disorders in sub‐Saharan Africa: A systematic review and meta‐analysis

Habte Belete,
Tesfa Mekonen Yimer,
Danielle Dawson
et al.

Abstract: Background and aimsPopulation‐level alcohol use data are available from high‐income countries, but limited research has been conducted in sub‐Saharan Africa. This systematic review and meta‐analysis aimed to summarize population‐level alcohol use in sub‐Saharan Africa.MethodDatabases searched included PubMed, EMBASE, PsycINFO and AJOL, without language restrictions. Searches were also conducted in the Global Health Data Exchange (GHDx) and Google Scholar. Search terms encompassed ‘substance’ or ‘substance‐rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…SSA covers a large area consisting of more than 50 countries, people of many different ethnic groups and varying economic and political systems [2]. In the first systematic review of its kind for the region, which includes 141 articles and just over half a million people, Belete and colleagues [3] present prevalence rates of alcohol use, alcohol use disorders and alcohol dependence among adults and adolescents across this diverse region. A previous systematic review of alcohol use across the continent was restricted to adolescents [4].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…SSA covers a large area consisting of more than 50 countries, people of many different ethnic groups and varying economic and political systems [2]. In the first systematic review of its kind for the region, which includes 141 articles and just over half a million people, Belete and colleagues [3] present prevalence rates of alcohol use, alcohol use disorders and alcohol dependence among adults and adolescents across this diverse region. A previous systematic review of alcohol use across the continent was restricted to adolescents [4].…”
mentioning
confidence: 99%
“…The findings point to a need for a deeper understanding of the socio-cultural underpinnings of alcohol consumption in the different areas of the continent. For example, Belete et al [3] found that when Muslimmajority countries (and others that have a prohibition against alcohol) were excluded from the analyses, rather than increasing, the weighted lifetime prevalence of alcohol consumption decreased from 23.3% (CI = 11.8-37.1) to 14.1% (CI = 0.0%-41.8%) for adolescents (although the confidence overlapped). Among adults, the weighted lifetime prevalence of alcohol use was 34.9% (CI = 17.7%-54.1%) for all countries and higher at 39.3% (CI = 26.7%-52.6%) when those countries were excluded.…”
mentioning
confidence: 99%
See 1 more Smart Citation